BYPASS1-LIKE, A DUF793 Family Protein, Participates in Freezing Tolerance via the CBF Pathway in Arabidopsis - Chen, Tao; Chen, Jia-Hui; Zhang, Wei; Yang, Gang; Yu, Li-Juan; Li, Dong-Ming; Li, Bo; Sheng, Hong-Mei; Zhang, Hua; An, Li-Zhe (Frontiers in Plant Science, 2019)
The C-REPEAT BINDING FACTOR signalling pathway is strictly modulated by numerous factors and is essential in the cold response of plants. Here, we show that the DUF793 family gene BYPASS1-LIKE modulates freezing tolerance through the CBFs in Arabidopsis. The expression of B1L was rapidly induced under cold treatment. Comparing to wild type, B1L knockout mutants were more sensitive to freezing treatment, whereas B1L-overexpressing lines were more tolerant. The expression of CBFs and CBF target genes was significantly decreased in b1l mutant. Using yeast two-hybrid screening system, 14-3-3λ was identified as one of proteins interacting with B1L. The interaction was confirmed with bimolecular fluorescence complementation assay and co-immunoprecipitation assay. Biochemical assays revealed that b1l mutation promoted the degradation of CBF3 compared to wild type, whereas 14-3-3κλ mutant and b1l 14-3-3κλ mutant suppressed the degradation of CBF3. Consistently, 14-3-3kλ and b1l 14-3-3kλ mutants showed enhanced freezing tolerance compared to wild type. These results indicate that B1L enhances the freezing tolerance of plants, at least partly through stabilizing CBF. Our findings improve our understanding of the regulation of CBF in response to cold stress.